Assessing hemorrhagic shock: Feasibility of using an ultracompact photoacoustic microscope. Issue 4 (13th December 2018) - Chen, Qian; Guo, Heng; Qi, Weizhi; Gan, Qi; Yang, Lei; Ke, Bowen; Chen, Xingxing; Jin, Tian; Xi, Lei
Abstract : Hemorrhagic shock, as an important clinical issue, is regarding as a critical disease with a high mortality rate. Unfortunately, existing clinical technologies are inaccessible to assess the hemorrhagic shock via hemodynamics in microcirculation. Here, we propose an ultracompact photoacoustic microscope to assess hemorrhagic shock using a rat model and demonstrate its clinical feasibility by visualizing buccal microcirculation of healthy volunteers. Both functional and morphological features of the microvascular network including concentration of total hemoglobin (CHbT ), number of blood vessels (VN), small vascular density (SVD) and vascular diameter (VD) were derived to assess the microvascular hemodynamics of different organs. Animal studies show the feasibility of the proposed tool to assess and stage the hemorrhagic shock via microcirculation. in vivo oral imaging of healthy volunteers indicates the translational possibility of this technique for clinical evaluation of hemorrhagic shock. Abstract : Hemorrhagic shock is a critical disease with a high mortality rate. We developed an ultracompact photoacoustic microscope to investigate the hemodynamics during the entire course of hemorrhagic shock. We evaluate the microvasculature in brain and three internal organs during hypotension and blood perfusion stages of hemorrhagic shock. The figure shows the design of imaging probe and the photoacoustic imaging of brain, intestine, ovary and bladder, respectively.